2004
DOI: 10.1016/j.clpt.2004.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics of nelfinavir and M8 during pregnancy and post partum

Abstract: Nelfinavir exposure was reduced during pregnancy, and the reduction was statistically significant for C 12 . M8 concentrations were about 70% lower during pregnancy compared with post partum, suggesting either induction of hepatic cytochrome P450 (CYP) 3A4 or inhibition of CYP2C19, or both, during pregnancy. Because 8 of 11 women had subtherapeutic nelfinavir trough concentrations during pregnancy, the safety and efficacy of therapeutic drug monitoring should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
51
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 37 publications
(81 reference statements)
11
51
1
Order By: Relevance
“…Some researchers have provided evidence of a postpartum drop in metabolic capacity that could result in briefly elevated drug concentrations (i.e., higher than baseline) for some antidepressants during the first 6–8 weeks following delivery 20, 21, 22, 23, 24. Due to few postpartum observations our study can neither confirm nor rule out that such a refractory period occurs for antipsychotic agents.…”
Section: Discussionmentioning
confidence: 61%
“…Some researchers have provided evidence of a postpartum drop in metabolic capacity that could result in briefly elevated drug concentrations (i.e., higher than baseline) for some antidepressants during the first 6–8 weeks following delivery 20, 21, 22, 23, 24. Due to few postpartum observations our study can neither confirm nor rule out that such a refractory period occurs for antipsychotic agents.…”
Section: Discussionmentioning
confidence: 61%
“…Nellen et al (19) found that the mean nelfinavir concentration ratio was significantly lower in pregnant women. Van Heeswijk et al (24) reported a significant reduction in nelfinavir minimum plasma concentration, supported by an Angel et al (2) study showing a 2.5-fold increase in nelfinavir apparent oral clearance. However, these studies included a small number of pregnant women.…”
Section: /F) 355 Liters/h (50%); Apparent Volume Of Distribution (Vmentioning
confidence: 53%
“…HIV protease inhibitor drug levels are generally reduced during pregnancy [13][14][15][16], especially during the third trimester, because of metabolic and physiological changes associated with pregnancy [17]. In one study of lopinavir/RTV, compensation for the lower exposures required a dose increase to 533/133 mg twice daily (bid) from 400/100 mg bid in the third trimester to produce exposures similar to those in nonpregnant historical controls [7].…”
Section: Introductionmentioning
confidence: 99%
“…Atazanavir (ATV) is a potent, well-tolerated, once-daily (qd) HIV protease inhibitor, with established efficacy in both treatment-naïve and treatment-experienced adult, nonpregnant HIV-infected patients [11,12] and is included as a preferred treatment option for nonpregnant HIVinfected patients [2]. HIV protease inhibitor drug levels are generally reduced during pregnancy [13][14][15][16], especially during the third trimester, because of metabolic and physiological changes associated with pregnancy [17]. In one study of lopinavir/RTV, compensation for the lower exposures required a dose increase to 533/133 mg twice daily (bid) from 400/100 mg bid in the third trimester to produce exposures similar to those in nonpregnant historical controls [7].…”
mentioning
confidence: 99%